Evaluation of gellan gum film containing virgin coconut oil for transparent dressing materials - Ismail, Nur Arifah; Mohamad,, Siti Fatimah; Ibrahim, Maizatul Akma; Mat Amin, Khairul Anuar (Hindawi Publishing Corporation, 2014)
We examined the potential of virgin coconut oil (VCO) incorporated in gellan gum (GG) films as a dressing material. Pure GG film is extremely brittle and inclusion of 0.3% (w/w) VCO in the GG film (GG-VCO3) improved the toughness ( J g−1) of the composite films. Swelling properties and water vapor transmission rates of GG-VCO composite films decreased, whereas thermal behavior values increased upon the addition of higher concentrations of VCO. Cell studies exhibit that the VCO is noncytotoxic to human skin fibroblast cells (CRL2522) with limited cell growth observed on GG-VCO3 films at 1,650 cells/well after incubation for 72 h which could be due to hydrophobic influence of the material surface. The qualitative and in vitro quantitative antibacterial results revealed that VCO does not possess strong bacterial resistance against all four tested bacteria, that is, two Gram-positive (Staphylococcus aureus and Staphylococcus epidermidis) and two Gram-negative bacteria (Pseudomonas aeruginosa and Proteus mirabilis).